Relationship Between Knowledge Sharing and Innovative Work Behaviour: The Role of Flexible Work Arrangement - Nguyen, Thuy Phuong; Pham, Quoc Trung (UI Scholars Hub, 2025)
Research Aims: To examine the influence of Knowledge Sharing (KS) on Innovative Work Behaviour (IWB) of employees in the IT industry, as well as the role of Flexible Work Arrangement (FWA) in this relationship. Design/Methodology/Approach: A survey was conducted gathering responses of employees of IT companies in Ho Chi Minh City. PLS-SEM approach was employed by using the SmartPLS application to analyse the model. Research Findings: A significant impact of Theory of Planned Behaviour factors, which are Attitudes toward a behaviour, Subjective Norms, and Perceived Behaviour Control on KS Intention was found, leading to a significant relationship with KS Behaviour. The finding confirmed that IWB is significantly impacted by KSB and FWA, while there is no significant relationship between FWA and KSB. Theoretical Contribution/Originality: Applicability of the TPB model in KSB prediction in the IT work environment was confirmed. Also, FWA directly positively impacts IWB asserts that apart from the collaborative knowledge behaviour path, an individual-driven innovation path should be considered as a path to innovation in organisations. Managerial Implication in the South East Asian Context: To bridge the gap between intention and actual KS, managers should cultivate a knowledge-sharing culture, implement mentorship programmes, and integrate KS into performance evaluations. Additionally, while FWA directly supports innovation, organisations should optimise digital communication tools and work models to maintain effective knowledge exchange and collaboration. Research Limitation & Implications: The data were collected using the convenience sampling method, limiting the generalisability of the findings. Moreover, FWA can be considered as a control variable or mediator to test its impact on the relationships among constructs in future research.